Double-blind comparison of venlafaxine and amitriptyline in outpatients with major depression with or without melancholia - Gentil, Valentim; Tiosso, Ana; Benedictis, Eliana; Kerr-Correa, Florence; Moreno, Ricardo; D'Arrigo Busnello, Ellis; Campos, João Alberto de; Juruena, Mario Francisco; Lafer, Beny; Moreno, Doris Hupfeld; Rosa, Lucena de Cássia Rodrigues (SAGE Publications, 2000)
The purpose of this study was to compare the efficacy and tolerability of venlafaxine and amitriptyline in outpatients with major depression with or without melancholia. This was an 8-week, multicentre, randomized, double-blind, parallel-group comparison of venlafaxine and amitriptyline. Outpatients with DSM-IV major depression, a minimum score of 20 on the 21-item Hamilton Depression Rating Scale (HAM-D), and depressive symptoms for at least 1 month were eligible. Patients were randomly assigned to venlafaxine or amitriptyline, both drugs titrated to a maximum of 150 mg/day until study day 15. The primary efficacy variables were the final on-therapy scores on the HAM-D, Montgomery-Asberg Depression Rating Scale and Clinical Global Impression severity scales. Data were evaluated on an intent-to-treat basis using the LOCF method. One hundred and 16 patients were randomized, and 115 were evaluated for efficacy. Both drugs showed efficacy in the treatment of depression with or without melancholia. No significant differences were noted between treatments for any efficacy parameter. However, significantly (p < 0.05) more patients in the amitriptyline group had at least one adverse event. These results should support the efficacy and tolerability of venlafaxine in comparison with amitriptyline for treating major depression with or without melancholia.
Keywords: Amitriptyline; Depression; Melancholia; Venlafaxine; amitriptyline; venlafaxine; adult; appetite disorder; clinical trial; constipation; controlled clinical trial; controlled study; data analysis; depression; disease severity; double blind procedure; drug efficacy; drug tolerability; female; Hamilton scale; headache; human; hypertension; insomnia; major clinical study; male; melancholia; multicenter study; nausea; outpatient care; paresthesia; priority journal; randomized controlled trial; rash; rating scale; somnolence; sweating; symptom; taste disorder; tremor; vertigo; visual impairment; xerostomia; Adolescent; Adult; Ambulatory Care; Antidepressive Agents, Second-Generation; Antidepressive Agents, Tricyclic; Cyclohexanols; Depressive Disorder; Depressive Disorder, Major; Double-Blind Method; Female; Humans; Male; Middle Aged; Personality Inventory; Treatment Outcome